Immunopathological Aspects of Experimental Trypanosoma cruzi Reinfections. (24th June 2014) - Reis Machado, Juliana; Silva, Marcos Vinícius; Borges, Diego Costa; da Silva, Crislaine Aparecida; Ramirez, Luis Eduardo; dos Reis, Marlene Antônia; Castellano, Lúcio Roberto; Rodrigues, Virmondes; Rodrigues, Denise Bertulucci Rocha
Abstract : Chagas disease is caused by Trypanosoma cruzi infection. Besides the host-related factors, such as immune response and genetic background, the parasite, strain, and occurrences of reinfection episodes, may influence disease outcome. Our results demonstrate that both the primary infection and the reinfection with the Colombiana strain are connected with lower survival rate of the mice. After reinfection, parasitaemia is approximately ten times lower than in primary infected animals. Only Colombiana, Colombiana/Colombiana, and Y/Colombiana groups presented amastigote nests in cardiac tissue. Moreover, the mice infected and/or reinfected with the Colombiana strain had more T. cruzi nests, more intense inflammatory infiltrate, and higher in situ expression of TNF- α and IFN- γ than Y strain. Antigen-stimulated spleen cells from infected and/or reinfected animals produced higher levels of TNF- α, IFN- γ, and IL-10. Our results reinforce the idea that Chagas disease outcome is influenced by the strain of the infective parasite, being differentially modulated during reinfection episodes. It highlights the need of control strategies involving parasite strain characterization in endemic areas for Chagas disease.